Non-print media [soundrecording] - Minow, Newton N.; American Library Association. Conference (91st). (Los Angeles, Calif. CREDR Corp., 1973)
In-depth discussion of the history and the role of educational and cable television. Explains the rationale behind past rulings of the Federal Communications Commission as well as pending legislation. In an extensive question and answer session, suggests that one solution to the pollution crisis is to reduce unnecessary transportation by working, educating, and even shopping at home through cable television.
American Library Association, 91st annual conference. Media: man, material, machine.
Keywords: Educational television stations -- Congresses; Cable television -- Congresses; Television in education -- Congresses; Education; Communication; Mass communication; Library science